Italy and the Second World War : alternative perspectives - Sica, Emanuele 1975- HerausgeberIn; Carrier, Richard C. 1969- HerausgeberIn (History of warfare, 2018)
"Italy in the Second World War: Alternative Perspectives stems from the necessity to write an important page of Second World War history, by focusing on the Italian war experience, which has been overshadowed in international research by the attention given to its senior Axis partner. Drawing extensively on material from Italian and international archives, a team of Italian and international historians, led by Emanuele Sica and Richard Carrier, offers a broad-ranging volume on the war seen through the lens of Italian soldiers and civilians, and populations occupied by the Italian army. Contributors are: Luca Baldissara, Cindy Brown, Federico Ciavattone, Nicolò Da Lio, Paolo Fonzi, Francesco Fusi, Eric Gobetti, Federico Goddi, Andrea Martini, Niall MacGalloway, Amedeo Osti Guerrazzi, Paolo Pezzino, Matteo Pretelli, Nicholas Virtue."--Provided by publisher